Pengalaman Adaptasi dan Komunitas Mahasiswa Perantau Universitas Jember Asal Kebumen di Kabupaten Jember Jawa Timur - Lila Aisyah; Helen Dewi Herdiana; Imelda Hartono Putri (Jurnal Relasi Publik, 2023)
This research aims to find out about the adaptation experiences experienced by students from Kebumen studying at the University of Jember. The aim of this research is to find out how students from Kebumen adapt and deal with culture shock while living in Jember. In adapting, students from Kebumen were assisted by the Kebumen Student Association (PERHIMAK), which is a family-based association that helps students from Kebumen adapt while living in Jember. This research uses a qualitative method with a phenomenological approach as a constructivist paradigm and in-depth interviews as a data collection technique. Interviews were conducted with students from Kebumen who studied and migrated to the University of Jember who were adapting to the culture shock and what difficulties they experienced while in Jember. The results of this research describe the underlying motives for students from Kebumen to migrate and study at Jember University, the adaptation experiences they have had, and how they overcome culture shock and homesickness during the ongoing adaptation process.